Climate Change in Rwanda: The Observed Changes in Daily Maximum and Minimum Surface Air Temperatures during 1961–2014 - Ngarukiyimana, Jean Paul; Fu, Yunfei; Sindikubwabo, Celestin; Nkurunziza, Idrissa Fabien; Ogou, Faustin Katchele; Vuguziga, Floribert; Ogwang, Bob Alex; Yang, Yuanjian (Frontiers in Earth Science, 2021)
Rwanda has experienced high temperature rising phenomena over the last decades and hence, highly vulnerable to climate change. Temperature rise does not only contribute to the development of disease vectors (e.g., Malaria) but also becomes a burden to the people due to heat stress. This study examines the spatio-temporal variations of daily maximum and minimum surface air temperatures (Tmax and Tmin), and diurnal temperature range (DTR) over Rwanda during 1961−2014 at monthly, seasonal and annual time-scales by applying various statistical methods (e.g., ordinary least-square fitting and sequential Mann-Kendall statistical test) to data series from 24 meteorological stations in Rwanda. Based on the impact of topography, stations were divided into three regions; region one (R1) (1000−1500m), region two (R2) (1500−2000m) and region three (R3) (≥2000m). The results indicate that the trend of Tmax significantly increased in all regions in the past decades at the rates of 0.40, 0.43, 0.41, 0.45℃ in R1; 0.47, 0.43, 0.3, 0.49℃ in R2 and 0.46, 0.37, 0.34, 0.45℃ in R3 per decade in MAM, JJA,OND and annual time scales, respectively. Similarly, the Tmin a significant positive trend OND, MAM, JJA, and annual time series with the rates of 0.40, 0.42, 0.50and 0.51℃ per decade in R1; 0.50, 0.40, 0.46, 0.001℃ in R2 and 0.32, 0.16, 0.26, 0.33℃ in R3, respectively. The spatial distributions of Tmax and Tmin represent a warming trend over the whole country; however, the seasonal and annual Tmin exhibited sharp increasing trends in the mountainous region (R3) of the country. Tmin in all regions was above the mean of 1961-2014 except 1991, 1992 and 2001, indicating warming in recent time. The high rate of increase of Tmax observed in R3 (high altitude) is another confirmation of warming in Rwanda. Based on the mutation test, most of the abrupt changes in seasonal and annual Tmax and Tmin trends have been noted during 1984-1990. The current study suggests that future studies should focus on the factors responsible for the spatial and temporal variability of Tmax and Tmin in the target region.